2011
DOI: 10.1111/j.1439-0396.2011.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fish meal protein by surimi by‐product protein in the diet of blue gouramiTrichogaster trichopterusfingerlings

Abstract: Based on the nutrient requirement of Trichogaster trichopterus, a fish meal-based basal diet with 350 g/kg diet crude protein and 16.7 MJ/kg energy was formulated, in which the fish meal protein was replaced by surimi by-product protein at 0.0 (control), 12.5, 25, 50, 75 and 100% levels. The formulated diets were fed ad libitum to T. trichopterus fingerlings (4.80 ± 0.03 g) in triplicate groups for 45 days in a closed water system. Eighteen fibre-reinforced plastic tanks with 200 l of water were used for reari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Similar to our results on use of fish processing waste, it is reported that fish offal [22] and the fisheries bycatch and processing waste [24] can be used as dietary protein source in the diet of freshwater catfish and Nile tilapia, respectively. The good growth performance of fish fed surumi by-product in the present study is in agreement with our earlier findings for the same species [29]. Generally, freshwater fish processing waste meal and surimi by-product meal were thrown away by the fish processors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to our results on use of fish processing waste, it is reported that fish offal [22] and the fisheries bycatch and processing waste [24] can be used as dietary protein source in the diet of freshwater catfish and Nile tilapia, respectively. The good growth performance of fish fed surumi by-product in the present study is in agreement with our earlier findings for the same species [29]. Generally, freshwater fish processing waste meal and surimi by-product meal were thrown away by the fish processors.…”
Section: Discussionsupporting
confidence: 93%
“…Future fish diets will include a wide range of alternative ingredients, including combinations of ingredients from animal origins [1]. Several animal protein sources were evaluated to formulate the diets for different fish species such as poultry byproduct meal [2,7,8], meat and bone meal [2,7,9], blood meal [10][11][12], feather meal [2,13,14], a mixture of meat meal and blood meal [15], garden snail meal [16], poultry viscera meal [17], turkey meal [18,19], tad pole meal [20], fermented silage made from fish meal [21], shrimp meal, blood meal, maggot meal and tilapia meal [3], fermented fish offal [22,23], fishery by-catch and processing waste [24], fish waste meal [25], tuna by-products [26], a mixture of feather meal, chicken offal and maggot meal [27], a blend of animal protein comprised of meat and bone meal, poultry by-product meal and hydrolysed feather meal [5], chicken concentrate, poultry by-product blend and chicken egg concentrate [28] and surumi by-product meal [29].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the poor growth and nutrient utilization in fish fed diet containing freshwater fish processing waste may be due to presence of scales and fins (about 10-15 % of the total waste). The good growth performance of fish fed surumi by-product in the present study is in agreement with our earlier findings for the blue gourami, Trichogaster trichopterus (Mohanta et al 2013;Mohanta and Subramanian 2011). Several authors have reported that the snail meat and snail offal meal could be used as good protein source in formulating the fish diet (Okanlawon and Oladipupo 2010;Suresh 2007;Sogbesan et al 2006;Fagbuaro et al 2006).…”
Section: Discussionsupporting
confidence: 95%